Mitochondrial fission process 1 protein: a comprehensive review of its core roles in mitochondrial dynamics, disease, and therapeutic targets - Ran, Qingzhi; Gao, Chen; Xiang, Chunrong; He, Xuanhui; Zhang, Yongkang; Zhang, Yin; Chen, Hengwen (Frontiers in Cell and Developmental Biology, 2025)
Mitochondrial fission process 1 (MTFP1) has emerged as a central regulator of mitochondrial dynamics, playing indispensable roles in maintaining organellar integrity, bioenergetic homeostasis, and stress adaptation - particularly in high-energy-demand tissues such as cardiac and skeletal muscle. Mounting evidence implicates MTFP1 dysfunction in the pathogenesis of diverse diseases including cardiovascular disorders, myopathies, and cancer. Beyond its canonical role in mediating mitochondrial fusion-fission balance, recent studies have unveiled MTFP1’s multifaceted involvement in calcium signaling modulation, ROS metabolism, and mitochondria-ER communication networks, substantially expanding its functional repertoire in cellular physiology. The protein’s pleiotropic effects stem from its ability to integrate metabolic status with organelle dynamics and quality control mechanisms. Particularly noteworthy is MTFP1’s cell-type-specific regulation of the ROS-calcium axis, which appears critical for its differential impacts in disease states. These discoveries position MTFP1 as both a mechanistic linchpin connecting mitochondrial dynamics to cellular homeostasis and a promising but challenging therapeutic target requiring precise contextual modulation. Current research frontiers focus on elucidating tissue-specific regulatory mechanisms of MTFP1 activity, developing microenvironment-sensitive targeting strategies, and exploring its potential as a biomarker for mitochondrial dysfunction-related pathologies. This evolving understanding of MTFP1’s integrative functions opens new avenues for developing precision therapies targeting mitochondrial dynamics in energy-metabolism-linked diseases.